GRAMMATICAL COHESION IN â€œTHE MIRACLE WORKERâ€ MOVIE (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
This study attempts to analyze of the use of grammatical cohesion in â€œThe Miracle Workerâ€ movie script. The basic purpose of this present study is to investigate the frequent of grammatical cohesion in movie script and the function. This descriptive study found out that all the grammatical cohesions suggested by Hassan and Halliday can be seenÂ in this movie except nominal ellipsis. In addition, this research also found three important functions of references, two functions of substitute, six functions of conjunction and only one function of ellipsis.